Can Managerial Discretion Explain Observed Leverage Ratios? - Morellec, Erwan (Review of Financial Studies, 2004)
This article analyzes the impact of managerial discretion and corporate control mechanisms on leverage and firm value within a contingent claims model where the manager derives perquisites from investment. Optimal capital structure reflects both the tax advantage of debt less bankruptcy costs and the agency costs of managerial discretion. Actual capital structure reflects the trade-off made by the manager between his empire-building desires and the need to ensure sufficient efficiency to prevent control challenges. The model shows that manager-shareholder conflicts can explain the low debt levels observed in practice. It also examines the impact of these conflicts on the cross-sectional variation in capital structures.